A Goal Programming Model for Planning Officer Accessions - Bres, E. S.; Burns, D.; Charnes, A.; Cooper, W. W. (Management Science, 1980)
A goal programming model for planning officer accessions to the U.S. Navy from various commissioning sources is developed and described. Present and future requirements for different career specialty areas in the Navy are considered in terms of years of commissioned service and related to various “choke points” where inventories fall short of requirements in officer force structure. An illustration of the use of this model is provided which involves assessments of the effects of phasing out one comissioning source. Other uses and possible further extensions are also indicated for this model, which now forms a part of the Navy's manpower planning procedures.